Detection of Ehrlichia spp. and Theileria spp. in Hyalomma anatolicum ticks collected in Tajikistan - M. Yu. Kartashov; Yu. V. Kononova; I. D. Petrova; N. L. Tupota; T. P. Mikryukova; V. A. Ternovoi; F. H. Tishkova; V. B. Loktev (Вавиловский журнал генетики и селекции)
The objectives of our study were to survey the prevalence of genetic markers for Rickettsia spp., Ehrlichia spp., Anaplasma spp., Babesia spp., and Theileria spp. in Hyalomma anatolicum ticks collected in southwestern Tajikistan and to perform sequencing and phylogenetic analysis of fragments of the 16S rRNA gene and groESL ope-ron from Ehrlichia spp. and fragments of the 18S rRNA gene of Theileria spp. detected in H. anatolicum ticks. Hyalomma anatolicum ticks collected in the Tursunzade and Rudaki districts of Tajikistan were tested for DNA of Rickettsia spp., Ehrlichia spp., Anaplasma spp., Babesia spp., and Theileria spp. by PCR with specific primers. The amplified fragments were sequenced and analyzed. DNA of Ehrlichia spp. (3.3 %) and Theileria spp. (3.3 %) was detected only in H. anatolicum ticks collected from the Rudaki district, and DNA of Ehrlichia spp. (0.7 %) was found in H. anatolicum ticks from the Tursunzade district. Sequence analysis of fragments of the 16S rRNA gene and groESL operon from Ehrlichia spp. revealed high similarity to Ehrlichia spp. The Tajik isolates of Theileria spp. were genotyped as Theileriaannulata based on the analysis of 18S rRNA gene sequences. The phylogenetic analysis demonstrates that Ehrlichia spp. isolates are highly similar to Ehrlichia spp. circulating in China and Brazil. The isolate Tajikistan-5 is closely related to the putative novel species Ehrlichia mineirensis. The Tajik isolates of Theileria spp. were clustered with T. annulata isolates from Turkey, Iran, Pakistan, and China by phylogenetic analyses.